2017
DOI: 10.1007/s12011-017-1015-1
|View full text |Cite
|
Sign up to set email alerts
|

Foxo1 Attenuates NaF-Induced Apoptosis of LS8 Cells through the JNK and Mitochondrial Pathways

Abstract: Fluoride-induced ameloblast apoptosis is a key event in dental fluorosis development. Forkhead box o1 (Foxo1) is a transcription factor involved in cell apoptosis. The present study aims to investigate the effect of Foxo1 on ameloblast apoptosis induced by fluoride in vitro and to explore its possible mechanism. Ameloblast-like cells (LS8 cells) were exposed to various concentrations of NaF for up to 48 h. Foxo1 activation was modulated using lentiviral vectors, and cell apoptosis was measured by flow cytometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Equol, which is a metabolite of daidzein, induces apoptosis in SMMC-7721 human hepatocellular carcinoma cells through the intrinsic and endoplasmic reticulum stress pathways (26). Caspase-9 and the Bcl-2/Bax ratio are commonly used activity markers of the mitochondrial apoptotic pathway (43)(44)(45). In the present study, western blotting was used to detect these markers, revealing that the cleavage of caspase-9 increased and the ratio of Bcl-2/Bax decreased in both cell lines in a dose-dependent manner, which indicated that daidzein-induced apoptosis was mediated via the mitochondrial apoptotic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Equol, which is a metabolite of daidzein, induces apoptosis in SMMC-7721 human hepatocellular carcinoma cells through the intrinsic and endoplasmic reticulum stress pathways (26). Caspase-9 and the Bcl-2/Bax ratio are commonly used activity markers of the mitochondrial apoptotic pathway (43)(44)(45). In the present study, western blotting was used to detect these markers, revealing that the cleavage of caspase-9 increased and the ratio of Bcl-2/Bax decreased in both cell lines in a dose-dependent manner, which indicated that daidzein-induced apoptosis was mediated via the mitochondrial apoptotic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have proposed potential molecular mechanisms underlying the prosurvival function of JNK, including autophagy . JNK can induce autophagy and counteract cancer cell apoptosis . In addition, a tumor immune evasion mechanism may be involved .…”
Section: Mechanisms By Which Jnk Regulates Cancer Cell Survivalmentioning
confidence: 99%
“…| 2091 apoptosis. 59 In addition, a tumor immune evasion mechanism may be involved. 60,61 JNK activates compensatory cell proliferation to maintain the balance between cancer cell death and survival.…”
Section: Mechanisms By Which Jnk Regulates Cancer Cell Survivalmentioning
confidence: 99%
See 1 more Smart Citation
“…5 and 8 days of continuous exposure revealed genetic damage and morphological alterations indicative of apoptosis by transmission electron microscopy as depicted by loss of cell-to-cell contact, nuclear chromatin condensation and apoptotic bodies (70). At the molecular level, rats treated with fluoride at 10 mg/kg for 5 weeks showed that caspase-9 and caspase-3, and the gene expressions of Bax were significantly increased (71).…”
Section: In Vivo Studiesmentioning
confidence: 99%